Perang Riau (1782-1787): Reflections on Maritime Culture in Tuhfat Al-Nafis - Setyadiharja, Rendra; Purnomo, Priyo Joko; Rahmat, Syahrul (Journal of Philology and Historical Review, 2023)
The Perang Riau is one of the events that is narrated completely in Tuhfat al-Nafis. This book was originally written by Raja Ahmad Engku Haji Tua and then perfected by Raja Ali Haji in the mid-19th century. Tuhfat al-Nafis discusses various events in the Malay region in full, including the maritime culture of the Malay people and naval warfare. As a historical work written by a Malay, Tuhfat al-Nafis offers an Indonesian-centric historiographic perspective regarding the Perang Riau. There are two problem formulations in this research, first, what are the aspects of Malay maritime culture in Tuhfat al-Nafis? And secondly, what is the narrative of maritime history in the events of the Perang Riau contained in Tuhfat al-Nafis. This research was carried out using historical research methods which consist of four stages, namely heuristics, source criticism, interpretation and historical writing. The results of the research show that Tuhfat al-Nafis explains well the maritime culture of the Malay community, especially with regard to shipping technology. Apart from that, control of geography, resources and maritime communities became the main capital for the Malays to survive and fight against the Dutch.